INVESTIGATION OF THE STABILITY OF A FOUR SPECIES MODEL INTERACTION BRINGING TO SYSTEMS OF TWO EQUATIONS - Tatyana Konstantinovna Pritula (Наука. Инновации. Технологии, 2022)
We propose a method to study the problem of stability of the structure of four interacting communities through information systems of two nonlinear differential equations of Lotka-Volterra, if the previously found the coordinates of the stationary points. Depth case check the stability of the stationary points with positive coordinates, when all community co-exist. The proposed algorithm and the program of research on the stability of the stationary state with non-zero coordinates of a mathematical model of the dynamics of four interacting communities.